Handbook on business information systems - Gunasekaran, Angappa; Sandhu, Maqsood Ahmad (World Scientific, 2010)
This handbook covers the vast field of business information systems, focusing particularly on developing information systems to capture and integrate information technology together with the people and their businesses. Part I of the book, "Health Care Information Systems", focuses on providing global leadership for the optimal use of health care information technology (IT). It provides knowledge about the best use of information systems for the betterment of health care services. Part II, "Business Process Information Systems", extends the previous theory in the area of process development by recognizing that improvements in intra-organizational business processes need to be complemented by corresponding improvements in inter-organizational processes. Part III deals with "Industrial Data and Management Systems" and captures the main challenges faced by the industry, such as the changes in the operations paradigm of manufacturing and service organizations. Finally, Part IV, "Evaluation of Business Information Systems", discusses the empirical investigation into the adoption of systems development methodologies and the security pattern of the business systems along with the mathematical models.